Os agentes funerários e a morte: o cuidado presente diante da vida ausente - Câmara, Cláudia Millena Coutinho da (2011)
The present time is marked by the art of escape from death, which has become synonymous with failure, its exposure has become intolerable and the care of the dead body were assigned to third parties who market this practice through services and products that shape the market undertaker. In this context, in which death is an object of study, has arisen funeral officers, as professionals dealing with a dead body, with the pain of relatives and their reactions, often being the first to have contact with the death scene. As professionals in the health area, the morticians also deal with death. The first attempt to prevent the arrival of death, funeral officers already has begun their work routine from there. Death and its surrounding part of their profession. What about those professionals whose work demands as a feared and denied by society? This study aims to understand the intents, meanings and implications for the mortician to deal with death in their daily work in order to focus renewed attention to the care of these professionals. To this end, it was carried out a qualitative research grounded in the theoretical framework of Gadamerian hermeneutics for production and interpretation of narratives. It was used two methodological strategies for data collection: in-depth interview with script and workshop with the use of "scenes". Research participants were nine morticians funeral of two funeral agencies of the city of Natal. It was possible to detect the presence of the social imaginary of interdiction on the theme of death from living with feelings of his presence daily, from the need of respondents to naturalize their contacts with death, a requirement of their office to deal with the difficulties of manipulating body fluids and odors, sometimes in a state of decomposition; allied to wishes to achieve the goal of delivering to family-customers a "embellished" body for the final farewell. Being a mortician, in addition to not being a professional motivation, involves facing difficulties related to heavy routine work, low salaries, unprofitable work materials and equipments, besides having to deal with the social gaze that devalues the profession. In turn, they also deal with the pain coming especially from contact with family members, either when they are targets of these feelings of anger, whether they identify with the pain of the bereaved ones. On the other hand, when the recognition and gratitude of the families occur, they find meaning and beauty in their profession of caring for the dead body. The present study by giving voice to morticians has become possible to understand better their profession, the pain that surrounds and care needs of these workers. Finally, it has argued that the mortician may be recognized as a care professional for the way exercising caution with the dead body and their families.